The "Rare Infliction": the Abolition of Flogging in the Indian Army, circa 1835–1920. (23rd May 2016) - Singha, Radhika
Abstract : "the very rarity is argument for retention" On September 2, 1920, an amendment to the Indian Army Act abolished corporal punishment for the Indian soldier and follower and introduced field punishment as a substitute on active service. This emancipation from the lash and the rattan came approximately 40 years after flogging had been abolished for the British soldier by the Army Discipline and Regulation Act, 1881. This article examines two distinct features of Indian military law during the high noon of empire: the Summary Court-Martial (SCM), introduced experimentally in the 1860s and formalized by Act V of 1869, and the prolonged retention of corporal punishment. The Manual of Indian Military Law described the SCM as a tribunal "peculiar to the Indian Army, " and the one most frequently used in it. There was no such tribunal under the British Army Act. The commanding officer (CO) of a "native" regiment presided as sole judge over an SCM, and in this capacity he could award a wide range of sentences, including corporal punishment of up to fifty lashes, and these sentences could be implemented forthwith, without confirmation from higher authority. The Manual of Military Law pronounced that for Indian troops in particular, "a slight punishment promptly inflicted" was more of a deterrent than a heavier one that followed long after the offense. However, from mid-century onwards, debates about flogging in the "native" army were usually inaugurated with the declaration that it was a punishment rarely used or that it was "practically obsolete." The issue offers one of those intriguing situations in which the rarity of a punishment becomes an argument for retaining it, instead of for doing away with it altogether.